Mixed modes and measurement error: Using cognitive interviewing to explore the results of a mixed modes experiment - Pamela Campanelli; Margaret Blake; Michelle Mackie; Steven Hope (University of Essex, Institute for Social and Economic Research (ISER), 2015)
This paper explores the use of cognitive interviewing as a pre-planned follow-up to a quantitative mixed modes experiment. It describes both the quantitative and cognitive interview phases and results. The goal for both was to explore measurement error differences between (computer-assisted personal interviewing - CAPI, computer-assisted telephone interviewing - CATI and computer-assisted web interviewing - CAWI). The cognitive interviewing produced evidence that in particular circumstances, supported or challenged the quantitative results. This is illustrated through the use of five examples. In conclusion, this novel application of cognitive interviewing was useful, with implications for survey design and interpretation of quantitative findings.
Keywords: C00; 330; cognitive interviewing; mixed modes; measurement error; satisficing; mode preferences; polar point; yes/no list